Integrative effects of increasing aridity and biotic cover on soil attributes and functioning in coastal dune ecosystems - Fernández-Alonso, Maria José (2021)
Climate change-driven increases in aridity will lead to dryland expansion worldwide. In the Atlantic and Mediterranean biogeographic regions, coastal dunes are priority conservation areas highly sensitive to aridification where plants and biological soil crusts may play a key role maintaining ecosystem services. However, we still need further insights into the balance between the effects of increasing aridity and the influence of local vegetation on the soil attributes and functioning of these systems, particularly in transitional areas between humid and arid climatic zones. We sampled 24 dune systems distributed along a natural climate gradient including humid, dry-subhumid and arid environments in the Atlantic coastline of the Iberian Peninsula and investigated (i) how aridity drives the vegetation community structure, soil biotic and abiotic properties and functions in dune ecosystems at a regional scale; and (ii) to what extent soil attributes differ locally under diverse surface microsites (i.e. plants, biocrust and bare soil). Increasing aridity in coastal dunes decreased total biotic cover and favoured the formation of shrub-dominated patches. Vegetation shifts were accompanied by declines in soil microbial diversity, organic matter, nutrient contents and reduced rates of N mineralization. Soil bacterial communities were more sensitive to aridity than fungal communities. Microsites were essential regulators of soil attributes, and their effects were dependent on the degree of aridity. In drylands, shrub microsites were associated to higher soil organic C, microbial (bacterial and fungal) abundance, fungal diversity and potential heterotrophic respiration than bare microsites, likely due to enhanced litter and sediment redistribution. However, at humid and transition systems, microsites controlled soil N pools and microbial diversity, suggesting tight linkages between vegetation patches and soil microorganisms responsible for N availability. These findings provide evidence of the strong negative impacts of aridification on vegetation attributes and nutrient cycling in coastal dunes and highlight the role of the biotic cover in preserving soil fertility, microbial diversity and functioning, particularly in the most arid sites